Karakter Morfologi dan Depresi Silang dalam Galur F4 Jagung Ungu Hasil Persilangan Bersari Bebas - Eries Dyah Mustikarini; Gigih Ibnu Prayoga; Yufikar Yufikar (Agrotechnology Research Journal, 2023)
Breeding of corn plants resulting from crosses experienced problems with inbreeding depression. Inbreeding depression can cause a decrease of good characters in maize lines. Information about inbreeding depression needs to be known so that it does not appear in the maize lines. This research aims to determine the presence of inbreeding depression  in purple corn lines from open pollinated and to determine the morphological character as a selection criterion for the F4 lines. Research using experimental methods. Plant selection was carried out using the ear-to-row method. Isolation of plants using distance and time of planting method. Observation of morphological characters using Royal Horticultural Society (RHS) Color Charts and the inbreeding depression test. F4 lines has inbreeding depression on the characters of plant height, stem diameter, number of leaves, male flowering age, female flowering age, cob length, cob weight with husk, cob weight without husk, and weight of 100 seeds . The F4 lines of corn plants that did not experience inbreeding depression on plant height and stem diameter characters in lines F4-PxU-11-25-18 and F4-PxU-11-25-25. Characters that can be used in the selection of F5 generation corn lines are plant height, stem diameter, cob length, cob weight with husk, cob weight without husk, and weight of 100 seeds. These characters can be used as selection criteria for the next generation.